Detection Of Mycobacterial Infection Using Filtrate Antigen - SOORAJ.S.NATH; NATHIYA.K; ANGAYARKANNI. J; PALANISWAMY.M (International Journal of Pharma and Bio Sciences, 2011)
Among infectious diseases, TB remains a leading cause of morbidity and mortality worldwide. Identification of tuberculosis infected individuals is essential in order to control the disease. Therefore there is a need for newer methods for rapid, sensitive and accurate diagnosis. In the present study, we have made use of antigens for the organism extracted from Mycobacterium tuberculosis H37Ra (ATCC 25177). ELISA technique performed gave sensitivity and specificity of 90% of TB in M. tuberculosis infected patients confirmed by culture. We conclude that the performance of extracted antigens is valuable in the diagnosis of TB.